Agricultural analysis and crop yield prediction of Habiganj using multispectral bands of satellite imagery with machine learning - Shahrin, Fariha; Zahin, Labiba; Rahman, Ramisa; Hossain, A S M Jahir (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.